PEMANTAPAN KOMITE PEMBELAJARAN DALAM MENGHADAPI KENAIKAN KELAS PADA FASE D DI SEKOLAH PENGGERAK SMP N 4 PATUK - Palupi Sri Wijayanti; Ratna Herawati; Rika Novita Sari; Kristina Warniasih; Fitri Jamilah (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2022)
Sekolah Penggerak is a school that implements an independent curriculum. SMP N 4 Patuk is one of those who are included in the first batch. End of school year activities must provide reports on student learning outcomes and confirmation of grade promotion. The first batch of driving schools have not found examples or best practices in compiling the document. Thus, there is a need for mentoring and strengthening of the learning committee in completing grade promotion documents. This is the basic foundation for the implementation of service and is carried out through three steps, namely preparation, implementation, and closing. At firts stage, the team communicated for permits from both schools and universities. In addition, the service team prepares materials related to the preparation of learning outcomes reports. Next is the implementation stage, the team conveys the material and then continues with discussions. In the last stage, which is closing, the servant conducts a simulation of filling out report for the Projek Profil Pelajar Pancasila activities. The results of the service activities for the learning committee showed an increase in the understanding and enthusiasm of the teachers in driving the transformation of the Sekolah Penggerak